Augmented Reality Media Development for Human Digestive Material to Afford The Learn Motivation of High School Student on SMA Kartika I-2 Medan - Khairunna Abdilla; Efrida Pima Sari Tambunan (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Based on interviews was conducted at Kartika I-2 Medan High School the biology teacher at Kartika I-2 Medan High School confirmed that there are currently no technology-based learning resources available to help biology students learn about the human digestive system, Furthermore, known that acquisition of the average of the mid-semester term score was 53.35. So that certain students experience boredom when learning, unfocused and less active in the learning process, it is also found that students lack understanding of several biology learning materials, one of which is the digestive system. This research was carried out on Kartika I-2 Medan High School which consists of 3 science class. The respondent of product test consists of 70 students in science class of second grade (XI-MIPA Class). The research instrument is a validity instrument, namely media/material expert validation. This learning media was developed through 4-D stages (Definition, Design, Development, Dissemination). Results showed that the application of augmented reality media to evaluate student motivation at Kartika I-2 Medan High School especially on the human digestive system. Media experts' validation results were 100% with very feasible criteria, while material experts' results revealed 93.5% with extremely viable criteria.  Thus, the learning process could take advantage of this augmented reality content.